Literature Review Exposure To Electric Cigarette Smoke (Vape) On Cerebrum And Rat Behavior - Woen, Aurelia Wirasdita; Sumbayak, Erma Mexcorry (Universitas Kristen Krida Wacana, 2024)
E-cigarettes are a modern form of conventional cigarettes, many have used them because they contain nicotine and various flavors so that young people like them. This literature aims to determine the effects of exposure to e-cigarettes containing nicotine or not on the cerebrum and behavior of experimental animals. The method of making literature in the form of literature review with a comprehensive approach. By searching for articles or journals in research journal databases, internet, articles. The database search used was Google Scholar, Pubmed, Proquest. Exposure to e-cigarette smoke can cause damage to the cerebrum, such as inflammation to necrosis, besides it can cause decreased cognitive abilities, behavior to emotional. E-cigarettes contain various components that are dangerous if consumed for a long time can cause dependence, decreased cognitive memory function and emotional changes. Exposure to secondhand smoke also causes inflammation, damage or necrosis. Nicotine also plays a role in this.